Maternal well-being and family adaptation during COVID-19 in fragile X syndrome - Fielding-Gebhardt, Heather; Swinburne Romine, Rebecca; Bredin-Oja, Shelley; Brady, Nancy; Warren, Steven F. (Frontiers in Psychiatry, 2022)
Mothers of children with fragile X syndrome are at increased risk of experiencing anxiety and depression due to potential genetic risk and to stress associated with parenting a child with significant behavioral, emotional, and educational support needs. During the initial shutdown and subsequent restrictions of the COVID-19 pandemic, mothers of children with fragile X reported experiencing elevated levels of anxiety and depression relative to their usual levels of well-being. Many indicated that the negative consequences of exposure to COVID-19 and related stressors, as well as the impacts of the pandemic on their family, directly affected their anxiety and depression. Mothers reported on specific sources of distress as well as potential sources of resilience and positive adaptation that occurred during the first year of the COVID-19 pandemic.